Percutaneous treatment of biliary cast syndrome after orthotopic liver transplantation: comparison of mechanical versus hydraulic rheolytic cast extraction - López-Benitez, Rubén; Wielpütz, Mark Oliver; Bryant, Mark; Ganten, Tom M.; Richter, G. M.; Flach, Nicole; Hallscheidt, Peter (CardioVascular and interventional radiology, 2011)
Biliary cast syndrome (BCS) is the presence of casts within the intrahepatic or extrahepatic biliary system after orthotopic liver transplantation. Our work compares two percutaneous methods for BCS treatment: the mechanical cast-extraction technique (MCE) versus the hydraulic cast-extraction (HCE) technique using a rheolytic system.